Application of catechol composite nonwoven fabric in synergistic persulfate degradation of trace antibiotics in water
By synergistically activating persulfate with catechol/polyethyleneimine composite nonwoven fabric, the limitations of the Fe2+ activated persulfate system were overcome, achieving efficient and stable degradation of antibiotics in water, avoiding the reuse of Fe2+ and the introduction of reducing agents, with a degradation rate of 88.20%-93.94%.
Patent Information
- Application Number
- CN202310954085.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-12-02
- Estimated Expiration
- 2043-07-31
AI Technical Summary
Existing Fe2+ activated persulfate systems have limitations in treating organic wastewater, as they are difficult to effectively control Fe2+ concentration to avoid free radical quenching reactions, resulting in low degradation efficiency.
Using catechol/polyethyleneimine composite nonwoven fabric as the substrate, Fe3+ is used to activate persulfate through complexation and reduction, thereby avoiding the introduction of additional reducing agents and enhancing the catalytic degradation ability.
It achieves efficient degradation of trace antibiotics in water under weakly alkaline conditions at room temperature. The material is easy to recycle, avoiding repeated addition of Fe2+ and secondary pollution. The degradation efficiency is as high as 88.20%-93.94%.
Smart Images

Figure CN116903121B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water pollution control technology, and in particular relates to the application of catechol composite nonwoven fabric in synergistic degradation of trace antibiotics in water by persulfate. Background Technology
[0002] Nowadays, with the frequent detection of various antibiotics and endocrine disruptors, among other organic pollutants, in water bodies, these substances tend to accumulate in organisms and are difficult to degrade by microorganisms, posing a significant threat to the natural environment and biological health. Compared to traditional water treatment technologies such as physical treatment, biological treatment, and membrane filtration, the removal of these pollutants from water bodies typically employs low-cost, high-efficiency advanced oxidation technologies.
[0003] Fenton's reagent, permanganate, permonosulfate (PMS), perdisulfate (PDS), and ozone are commonly used in advanced oxidation treatment of wastewater. Advanced oxidation processes based on sulfate radicals (SR-AOPs) are attracting increasing attention due to their low cost, high catalytic activity, long radical half-life, wide applicability, and high selectivity for complex systems in aquatic environments.
[0004] Currently, iron-based catalysts are widely used in advanced oxidation technologies due to their low cost, high catalytic activity, and easy recovery. However, existing Fe... 2+ The activated persulfate system for treating organic wastewater still has certain limitations, and many studies focus on how to control Fe. 2+ The concentration of Fe 2+ This approach effectively activates persulfate while minimizing the quenching reaction of free radicals, thus fully utilizing free radical oxidation to degrade target pollutants. Therefore, seeking efficient and continuous activation methods to promote the generation of active free radicals from persulfate for further degradation of PPCPs wastewater has become a crucial breakthrough in advanced oxidation processes. Summary of the Invention
[0005] In view of this, the present invention aims to propose an application of catechol composite nonwoven fabric in the synergistic degradation of trace antibiotics in water by persulfate. The operation method of the present invention is simple, utilizing the strong adhesion behavior of catechol and polyethyleneimine to degrade trace antibiotics in water. 3+ The complexation and reduction effects, as well as the synergistic promotion of persulfate activation, effectively control the Fe content in the system. 3+ Fe 3+ Its ability to activate PMS is relatively poor, but compared to Fe... 2+ More stable, can avoid Fe 2+ The catechol / polyethyleneimine composite nonwoven fabric, which is prone to oxidation, can effectively reduce Fe in the system during the reaction process. 3+No additional reducing agent needs to be introduced during the reaction, while simultaneously enhancing the Fe... 3+ The catalytic degradation capability of the / PMS system for organic pollutants.
[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows:
[0007] A method for preparing a catechol / polyethyleneimine composite nonwoven fabric for synergistic persulfate degradation of antibiotics includes the following steps:
[0008] (1) Clean and dry the nonwoven fabric for later use;
[0009] (2) Dissolve catechol and polyethyleneimine in tris(hydroxymethyl)aminomethane hydrochloride buffer solution to prepare a precipitation solution; the mass ratio of catechol to polyethyleneimine is 1-4:1; the concentration of tris(hydroxymethyl)aminomethane hydrochloride buffer solution is 0.005-0.05 mol / L, and the pH is 8-8.5;
[0010] (3) The nonwoven fabric obtained in step (1) is placed in the deposition liquid obtained in step (2) for oscillation reaction, and dried to obtain catechol / polyethyleneimine composite nonwoven fabric.
[0011] Preferably, in step (1), the nonwoven fabric is one of polypropylene spunbond nonwoven fabric, polyethylene spunbond nonwoven fabric, and polyester spunbond nonwoven fabric.
[0012] Preferably, in step (1), the nonwoven fabric is ultrasonically cleaned with deionized water or ethanol or a mixture of both, and the drying temperature is 60℃-70℃.
[0013] Preferably, in step (2), the concentration of the tris(hydroxymethyl)aminomethane hydrochloride buffer solution is 0.01-0.05 mol / L.
[0014] Preferably, in step (2), the concentration of catechol in the sediment is 1 g / L-8 g / L.
[0015] Preferably, in step (3), the total loading of catechol and polyethyleneimine in the catechol / polyethyleneimine composite nonwoven fabric is 30%-50%.
[0016] Preferably, in step (3), the temperature of the oscillation reaction is 10-25℃ and the reaction time is 8-24h.
[0017] The present invention also provides the application of catechol / polyethyleneimine composite nonwoven fabric prepared by the preparation method described above in the synergistic degradation of trace antibiotics in water by persulfate.
[0018] Preferably, the antibiotic is one or both of carbamazepine and bisphenol A, and the concentration of the antibiotic in the solution is 5-20 mg / L.
[0019] Preferably, the conditions for catalytic degradation are: temperature 10-25℃, pH 3-8, persulfate dosage 0.5-2 mmol / L, ferric salt or ferrous salt dosage 0.25-2 mmol / L, and catechol / polyethyleneimine composite nonwoven fabric dosage 0.05-0.5 g / L.
[0020] Antibiotics include carbamazepine (CBZ) and bisphenol A (BPA).
[0021] Compared with existing technologies, the application of the catechol composite nonwoven fabric synergistically with persulfate degradation of trace antibiotics in water described in this invention has the following advantages:
[0022] The nonwoven fiber material in this invention serves as a composite substrate for catechol and polyethyleneimine, facilitating recycling after wastewater treatment. Catechol, as a dopamine-like substance, exhibits a simple self-polymerization process under mild reaction conditions, achievable in a weakly alkaline, room-temperature air atmosphere. Its functional groups can interact with various substrates to form anchor points, while simultaneously forming covalent bonds through oxidative coupling. Intermolecular bonding can also occur through hydrogen bonding and π-π stacking to form non-covalent cross-linked structures. Furthermore, the introduction of a second functional polymer, polyethyleneimine, modulates the interaction of catechol functional groups with Fe... 3+ The complexation effect optimizes the mechanical properties and stability of the functional composite cross-linked layer. Catechol and polyethyleneimine functional groups form a composite cross-linked layer on the outer surface of the fiber. This heterogeneous system exhibits good mass transfer performance during the activation of persulfate. This invention can utilize Fe... 3+ Instead of only being able to use Fe 2+ In the further catalytic oxidation degradation process, Fe can be avoided. 2+ Repeated addition of Fe during the reaction process leads to the complexation and reduction of Fe. 3+ This effectively avoids the consumption of reactive species such as free radicals in the system by iron ions, and also eliminates the need for sequential batch addition of reducing agents, preventing secondary pollution. When synergistically activating persulfate to degrade organic pollutants in water, it promotes the reduction of iron ions in the system. Furthermore, the catechol and quinone groups on the material surface can generate semiquinone free radicals in the reaction system, which in turn activate persulfate to generate sulfate free radicals. This further ensures that the degradation process can proceed continuously, efficiently, and stably. Attached Figure Description
[0023] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:
[0024] Figure 1 This is a scanning electron microscope image of the catechol / polyethyleneimine composite nonwoven fabric prepared in Example 1 of this invention;
[0025] Figure 2 This is a graph showing the degradation efficiency versus time of the catechol / polyethyleneimine composite nonwoven fabric prepared in Example 1 of this invention in the synergistic activation of persulfate degradation of CBZ. Detailed Implementation
[0026] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other.
[0027] Unless otherwise defined, the technical terms used in the following embodiments have the same meaning as commonly understood by those skilled in the art; in this invention, unless otherwise specified, all raw materials used are commercially available products in the art.
[0028] This invention provides an application of catechol composite nonwoven fabric in the synergistic degradation of trace antibiotics in water by persulfate, the specific steps of which are as follows:
[0029] The preparation method of catechol / polyethyleneimine composite nonwoven fabric includes the following specific steps:
[0030] (1) After ultrasonically cleaning the polypropylene spunbond nonwoven fabric several times with deionized water and ethanol, place it in an oven at 70°C and dry it to constant weight. Cut the dried polypropylene nonwoven fabric into appropriate sizes for later use.
[0031] (2) Prepare a 0.01 mol / L tris(hydroxymethyl)aminomethane solution, adjust the pH to 8.5 with a 1 mol / L hydrochloric acid solution, weigh an appropriate amount of catechol and add it to the buffer solution, add polyethyleneimine after it dissolves, and adjust the mass ratio of catechol to polyethyleneimine to 1-4:1 to obtain the sediment.
[0032] (3) Place the PP nonwoven fabric washed in step (1) into the deposition solution and shake it in a constant temperature shaker at 25°C for 8 to 24 hours. Take out the composite material after the reaction, rinse its surface with deionized water, dry it, weigh it and record the load to obtain catechol / polyethyleneimine composite nonwoven fabric (hereinafter referred to as CT / PEI@PP).
[0033] Degradation of organic pollutants in water
[0034] Add 200 mL of the prepared organic pollutant solution to a 250 mL beaker, adjust the pH of the solution, and add catechol / polyethyleneimine composite nonwoven fabric, FeSO4 or FeCl3 and potassium persulfate respectively. React for 90 min under magnetic stirring at 25 °C.
[0035] Example 1
[0036] The preparation method of catechol / polyethyleneimine composite nonwoven fabric includes the following specific steps:
[0037] (1) After ultrasonically cleaning the polypropylene spunbond nonwoven fabric several times with deionized water and ethanol, place it in an oven at 70°C to dry to constant weight, cut it and set it aside for use.
[0038] (2) Prepare a 0.01 mol / L tris(hydroxymethyl)aminomethane solution, adjust the pH of the solution to 8.5 with 1 mol / L hydrochloric acid solution, prepare a Tris-HCl buffer solution, weigh 0.2 g catechol and add it to 100 mL of Tris-HCl buffer solution, dissolve it by sonication, and then add 0.2 g polyethyleneimine to the solution so that the mass ratio of catechol to polyethyleneimine is 1:1 to obtain the sediment;
[0039] (3) The washed PP nonwoven fabric was wetted with anhydrous ethanol and then immersed in the deposition solution in step (2). It was placed in a constant temperature shaker at 25°C and shaken for 24 hours. The composite material after reaction was taken out, rinsed several times with deionized water, and dried at 70°C to obtain CT / PEI@PP. The total loading of catechol and polyethyleneimine was 35.8%.
[0040] The performance experiment of CT / PEI@PP in Example 1 is as follows:
[0041] A 200 mL solution of carbamazepine (CBZ) with an initial concentration of 10 mg / L was prepared. The pH of the solution was adjusted to 3 with 0.1 mol / L hydrochloric acid. Then, 0.1 g of CT / PEI@PP prepared in Example 1, 0.2 mmol of FeCl3, and 0.2 mmol of potassium persulfate (PMS) were added sequentially to the solution. The reaction was carried out at 25 °C with magnetic stirring for 90 min. The concentration of CBZ in the solution was determined by high-performance liquid chromatography (HPLC). The results showed that the degradation rate of CBZ reached 88.20% after 90 min of reaction.
[0042] Figure 1 This is a scanning electron microscope image of the catechol / polyethyleneimine composite nonwoven fabric in Example 1 of the present invention. As can be seen from the image, the catechol and polyethyleneimine polymers are uniformly distributed on the surface of the PP fabric, and no large agglomeration phenomenon is observed.
[0043] Figure 2 This is a graph showing the degradation efficiency versus time of the catechol / polyethyleneimine composite nonwoven fabric prepared in Example 1 of this invention during the synergistic activation of persulfate degradation of CBZ. Figure 2It can be concluded that the prepared catechol / polyethyleneimine composite nonwoven fabric can synergistically activate persulfate with iron, thereby rapidly degrading CBZ in solution.
[0044] Example 2
[0045] The preparation method of catechol / polyethyleneimine composite nonwoven fabric includes the following specific steps:
[0046] (1) After ultrasonically cleaning the polypropylene spunbond nonwoven fabric several times with deionized water and ethanol, place it in an oven at 70°C to dry to constant weight, cut it and set it aside for use.
[0047] (2) Prepare a 0.01 mol / L tris(hydroxymethyl)aminomethane solution, adjust the pH of the solution to 8.5 with a 1 mol / L hydrochloric acid solution, prepare a Tris-HCl buffer solution, weigh 0.2 g of catechol and add it to 100 mL of buffer solution, dissolve it by sonication, and then add 0.2 g of polyethyleneimine to the solution so that the mass ratio of catechol to polyethyleneimine is 1:1, and obtain the sedimentation solution;
[0048] (3) After wetting the cleaned PP nonwoven fabric with anhydrous ethanol, immerse it in the deposition solution in step (2), place it in a constant temperature shaker at 25°C and shake for 24 hours. Take out the composite material after reaction, rinse it several times with deionized water, and dry it at 70°C to obtain CT / PEI@PP with a loading of 35.8%.
[0049] The performance experiment of CT / PEI@PP in this Example 2 is as follows:
[0050] Prepare 200 mL of CBZ solution with an initial concentration of 10 mg / L. Adjust the pH of the solution to 3 with 0.1 mol / L hydrochloric acid. Then, add 0.1 g of CT / PEI@PP prepared in Example 2, 0.2 mmol of FeSO4·7H2O, and 0.2 mmol of PMS (potassium peroxymonosulfate) sequentially to the solution. React at 25 °C with magnetic stirring for 90 min. The concentration of CBZ in the solution is determined by high performance liquid chromatography.
[0051] Test results showed that the degradation rate of CBZ reached 87.93% after 90 minutes of reaction. Comparison revealed that the experiment using Fe... 3+ Activated PMS can degrade CBZ to achieve the effect of Fe 2+ The activation effect further demonstrates that the prepared CT / PEI@PP can reduce Fe during the reaction. 3+ This effectively regulates the Fe content in the system. 2+ / Fe 3+ The cycle.
[0052] Example 3
[0053] The preparation method of catechol / polyethyleneimine composite nonwoven fabric includes the following specific steps:
[0054] (1) After ultrasonically cleaning the polypropylene spunbond nonwoven fabric several times with deionized water and ethanol, place it in an oven at 70°C to dry to constant weight, cut it and set it aside for use.
[0055] (2) Prepare a 0.01 mol / L tris(hydroxymethyl)aminomethane solution, adjust the pH of the solution to 8.5 with a 1 mol / L hydrochloric acid solution, prepare a Tris-HCl buffer solution, weigh 0.8 g of catechol and add it to 100 mL of buffer solution, dissolve it by sonication, and then add 0.2 g of polyethyleneimine to the solution so that the mass ratio of catechol to polyethyleneimine is 4:1, and obtain the sediment;
[0056] (3) After wetting the cleaned PP nonwoven fabric with anhydrous ethanol, immerse it in the deposition solution in step (2), place it in a constant temperature shaker at 25°C and shake for 24 hours. Take out the composite material after reaction, rinse it several times with deionized water, and dry it at 70°C to obtain CT / PEI@PP with a loading of 50.0%.
[0057] The performance experiment of CT / PEI@PP in Example 3 is as follows:
[0058] A 200 mL solution of CBZ with an initial concentration of 10 mg / L was prepared. The pH of the solution was adjusted to 3 with 0.1 mol / L hydrochloric acid. Then, 0.1 g of CT / PEI@PP prepared in Example 3, 0.2 mmol FeCl3, and 0.2 mmol PMS were added sequentially. The reaction was carried out at 25 °C with magnetic stirring for 90 min. The concentration of CBZ in the solution was determined by high-performance liquid chromatography (HPLC). The results showed that the degradation rate of CBZ reached 79.61% after 90 min of reaction.
[0059] Example 4
[0060] A 200 mL solution of BPA with an initial concentration of 10 mg / L was prepared. The pH of the solution was adjusted to 3 using 0.1 mol / L hydrochloric acid. Then, 0.1 g of CT / PEI@PP prepared in Example 1, 0.2 mmol FeCl3, and 0.2 mmol PMS were added sequentially. The reaction was carried out at 25 °C with magnetic stirring for 90 min. The concentration of BPA in the solution was determined by high-performance liquid chromatography (HPLC). The results showed that the degradation rate of BPA reached 93.94% after 90 min of reaction.
[0061] Comparative Example 1
[0062] Compared with Example 1, the only difference in Comparative Example 1 is that FeCl3 was not added to the reaction system; all other reaction steps are the same as in Example 1.
[0063] A 200 mL solution of CBZ with an initial concentration of 10 mg / L was prepared. The pH of the solution was adjusted to 3 with 0.1 mol / L hydrochloric acid. Then, 0.1 g of CT / PEI@PP prepared in Example 1 and 0.2 mmol of PMS were added sequentially. The reaction was carried out at 25 °C with magnetic stirring for 90 min. The concentration of CBZ in the solution was determined by high-performance liquid chromatography (HPLC). The results showed that the concentration of CBZ changed very little after 90 min of reaction, indicating that although CT / PEI@PP can activate PMS to a small extent to produce active substances that degrade CBZ, it does not play a major role.
[0064] Comparative Example 2
[0065] Compared with Example 1, the only difference in Comparative Example 2 is that CT / PEI@PP was not added to the reaction system; all other reaction steps were the same as in Example 1.
[0066] A 200 mL solution of CBZ with an initial concentration of 10 mg / L was prepared. The pH of the solution was adjusted to 3 with 0.1 mol / L hydrochloric acid. Then, 0.2 mmol FeCl3 and 0.2 mmol PMS were added sequentially. The reaction was carried out at 25 °C with magnetic stirring for 90 min. The concentration of CBZ in the solution was determined by high-performance liquid chromatography (HPLC). The results showed that the degradation rate of CBZ reached 10.02% after 90 min of reaction. This indicates that CT / PEI@PP can effectively reduce Fe in the system. 3+ This ensures that Fe in the system 2+ / Fe 3+ This cycle further ensures that the system can operate continuously, stably, and efficiently.
[0067] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. The application of a catechol / polyethyleneimine composite nonwoven fabric in the synergistic degradation of trace antibiotics in water by persulfate, characterized in that: The antibiotic is one or both of carbamazepine and bisphenol A, and the concentration of the antibiotic in the solution is 5-20 mg / L; the conditions for catalytic degradation are: temperature 10-25℃, pH value 3-8, persulfate dosage 0.5-2 mmol / L, ferric salt or ferrous salt dosage 0.25-2 mmol / L, and catechol / polyethyleneimine composite nonwoven fabric dosage 0.05-0.5 g / L; The above-mentioned method for preparing catechol / polyethyleneimine composite nonwoven fabric for synergistic persulfate degradation of antibiotics includes the following steps: (1) Clean and dry the nonwoven fabric for later use; (2) Dissolve catechol and polyethyleneimine in tris(hydroxymethyl)aminomethane hydrochloride buffer solution to prepare a precipitation solution; the mass ratio of catechol to polyethyleneimine is 1-4:1; the pH is 8-8.5; (3) The nonwoven fabric obtained in step (1) is placed in the deposition liquid obtained in step (2) for oscillation reaction, and dried to obtain catechol / polyethyleneimine composite nonwoven fabric; In step (2), the concentration of the tris(hydroxymethyl)aminomethane hydrochloride buffer solution is 0.01 - 0.05 mol / L; In step (2), the concentration of catechol in the sediment is 1 g / L-8 g / L.
2. The application according to claim 1, characterized in that: In step (1), the nonwoven fabric is one of polypropylene spunbond nonwoven fabric, polyethylene spunbond nonwoven fabric, and polyester spunbond nonwoven fabric.
3. The application according to claim 1, characterized in that: In step (1), the nonwoven fabric is ultrasonically cleaned with deionized water or ethanol or a mixture of both, and the drying temperature is 60℃-70℃.
4. The application according to claim 1, characterized in that: In step (3), the total loading of catechol and polyethyleneimine in the catechol / polyethyleneimine composite nonwoven fabric is 30%-50%.
5. The application according to claim 1, characterized in that: In step (3), the temperature of the oscillating reaction is 10-25℃ and the reaction time is 8-24h.
Citation Information
Patent Citations
Agent and method for removing organic pollutants in water and application
CN113979530A